1998
DOI: 10.1074/jbc.273.10.5557
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of the Noncatalytic cGMP Binding Sites of Frog Photoreceptor Phosphodiesterase Using cGMP Analogs

Abstract: The cGMP-specific phosphodiesterase (PDE) of retinal photoreceptors is a central regulatory enzyme in the visual transduction pathway of vertebrate vision. Although the mechanism of activation of PDE by transducin is well understood, the role of the noncatalytic cGMP binding sites located on the catalytic subunits of PDE remains obscure. We report here for the first time the molecular basis of the noncovalent interactions between cGMP and the high affinity, noncatalytic cGMP binding sites of frog photoreceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…The general features of cGMP binding in the GAF B structure are consistent with many of the predictions made from binding studies of PDE2 and PDE6 with cyclic nucleotide analogues. These studies suggested that cGMP would be bound in the anti-conformation, that contacts are made to C6, N1, and C2 amino group of the guanine ring and 2ЈO of the ribose ring, and that there are similar or identical types of contacts to the exocyclic oxygens (21,26,34). (D) cGMP and cAMP competition binding curves [against ( 3 H)cGMP] for the wild-type regulatory segment of mouse PDE2A.…”
Section: Resultsmentioning
confidence: 99%
“…The general features of cGMP binding in the GAF B structure are consistent with many of the predictions made from binding studies of PDE2 and PDE6 with cyclic nucleotide analogues. These studies suggested that cGMP would be bound in the anti-conformation, that contacts are made to C6, N1, and C2 amino group of the guanine ring and 2ЈO of the ribose ring, and that there are similar or identical types of contacts to the exocyclic oxygens (21,26,34). (D) cGMP and cAMP competition binding curves [against ( 3 H)cGMP] for the wild-type regulatory segment of mouse PDE2A.…”
Section: Resultsmentioning
confidence: 99%
“…In PDE2, the cGMP-versuscAMP selectivity of the allosteric cN-binding sites is considerably lower, and other molecules may also interact with these sites to stimulate catalytic activity (Erneux et al, 1985;Manganiello et al, 1990;Martinez et al, 2002b). The specificity requirements for cGMP binding to the GAF(s) in PDEs 5 and 6 are the most restrictive of any known cN-binding protein, and these sites tolerate very few cN analogs (Francis et al, 1990;Hebert et al, 1998).…”
mentioning
confidence: 99%
“…In PDE2, cGMP is bound in the anticonformation of the N-glycosidic linkage, and the cyclic phosphate moiety is in the energetically unfavorable boat conformation. Earlier studies using cGMP analogs with PDE5 and PDE6 had predicted that cGMP is bound in the anti-conformation (Francis et al, 1990;Hebert et al, 1998).…”
mentioning
confidence: 99%
See 2 more Smart Citations